Internationell handel – En kvalitativ studie om handelsproblem när gods ej hämtas ut - Kaber, Jacob; Östergren Bööj, Jonathan (My University, 2016)
A trading company as well as two shipping companies has recognized the fact that problems sometimes occur. These are more specifically problems regarding issues when the consignee abandons his/her cargo and the containers carrying the cargo instead of collecting the goods at the port of discharge, which leads to parties being affected both economically and by the time consumed. This report will handle the three main questions; Why do problems occur on the subject of cargo carriers not being collected? How can the problem that arises when cargo carriers are not collected be eliminated? Can the seller conduct proactive measures in order to be better prepared for problems of cargo carriers not being collected? The report is based upon information from a trading company and two carriers. A large portion of the report has been worked on at the trading house in question, where regular interviews and discussions were conducted. The interviews with the two carriers were conducted using open questions and discussions using the semi-structured approach in pre-booked meetings and e-mails. Interviews in addition to discussions with the parties in the buyer’s country are non-existing. All parties involved are treated with utmost discretion. Both of the interviewed shipping companies mention that they have been faced with, or heard about similar problems. Therefore they have formed a process that enables them the right to overtake possession of property if the consignee, buyer, is not fulfilling his duties of collecting the containers containing the goods during the contractual designated timeframe.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics